Menstrual cycle among adolescents: girls' awareness and influence of age at menarche and overweight - Patrícia Marques; Tiago Madeira; Augusta Gama (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: To characterize the menstrual cycle (regularity and menstrual flow length), the prevalence of dysmenorrhea and self-monitoring of the cycle in students from Lisbon region, and explore the effect of chronological age, age at menarche and body mass index (BMI) on menstrual disorders. Methods: This is a cross-sectional study with 848 girls aged 12-18 years. A questionnaire about the sociodemographic context and characteristics of the menstrual cycle, and weight and height measures were assessed. BMI was classified according to International Obesity Taskforce criteria. A descriptive analysis of the variables was made, and Odds Ratios (ORs) and 95% confidence intervals (95%CIs) were determined. Results: Mean age at menarche was 12.4 years and mean BMI was 22.0kg/m2. Among adolescents, 59% have regular menstrual cycle, 83% have menstrual flow length of ≤6 days. 88% suffered from dysmenorrhea, among which 8,7% declare absenteeism from school and 49% took pain medication, and 65% self-monitor their menstrual cycle. Higher maternal education was associated with a higher self-monitoring of menstrual cycle among the sample (OR 1.60; 95%CI 1.15-2.17). Girls with menarche <12 years-of-age are more likely to have menstrual flow length of >6 days (OR 1.73; 95%CI 1.19-2.51) and dysmenorrhea (OR 1.87; 95%CI 1.11-3.16) than those with menarche ≥12 years-of-age. No significant association between BMI and menstrual cycle variables was observed. Conclusions: The results suggest that menstrual disorders are frequent and may be associated with early menarche, but not with BMI. It is important to encourage self-monitoring of the menstrual cycle to detect menstrual disorders timely and promote health and well-being.